2022
DOI: 10.3390/ijms23147591
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Atrial Fibrillation—State of the Art

Abstract: Extracellular vesicles are particles released from cells and delimited by a lipid bilayer. They have been widely studied, including extensive investigation in cardiovascular diseases. Many scientists have explored their role in atrial fibrillation. Patients suffering from atrial fibrillation have been evidenced to present altered levels of these particles as well as changed amounts of their contents such as micro-ribonucleic acids (miRs). Although many observations have been made so far, a large randomized cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…EVs have potential as biomarkers in the diagnosis, prognosis, and monitoring of atherosclerosis in patients and as new therapeutic targets and/or drug delivery vehicles [ 17 ]. It is worth mentioning that altered levels of EVs have been evidenced in patients suffering from atrial fibrillation [ 177 ]. They may be clinically useful as therapeutic targets in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…EVs have potential as biomarkers in the diagnosis, prognosis, and monitoring of atherosclerosis in patients and as new therapeutic targets and/or drug delivery vehicles [ 17 ]. It is worth mentioning that altered levels of EVs have been evidenced in patients suffering from atrial fibrillation [ 177 ]. They may be clinically useful as therapeutic targets in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These features allow ease of sample handling and result reproducibility, and thus potentially facilitate translation from bench to bedside use. Multiple studies have identified an association between the content of circulating EVs and AF [ 120 , 121 ]. A study by Shaihov-Teper et al analyzed EVs derived from the epicardial fat of individuals with (n = 32) and without AF (n = 30) [ 122 ].…”
Section: Perspective On Future Areas Of Researchmentioning
confidence: 99%
“…The search for biomarkers enabling diagnosis, prognosis, and treatment response prediction in different cardiovascular diseases has included not only various microparticles, such as micro-ribonucleic acids or extracellular vesicles, but also autoantibodies [21][22][23]. Autoantibodies have been found to target various cardiac receptors modulating the impact of the autonomic nervous system on signaling pathways [7,24].…”
Section: Introductionmentioning
confidence: 99%